2013
DOI: 10.1021/ja308852b
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Model for Amorphous Protein Aggregation of Immunoglobulin-like Domains

Abstract: Protein aggregation is associated with many debilitating diseases including Alzheimer’s, Parkinson’s, and light-chain amyloidosis (AL). Additionally, such aggregation is a major problem in an industrial setting where antibody therapeutics often require high local concentrations of protein domains to be stable for substantial periods of time. However, despite a plethora of research in this field, dating back over 50 years, there is still no consensus on the mechanistic basis for protein aggregation. Here we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 44 publications
(110 reference statements)
2
44
0
1
Order By: Relevance
“…The mutant dimer and trimer constructs maintain marginal stability. Our result for the wild-type construct is consistent with the aggregation experiments on I27 under denaturing conditions [28% Trifluoroethanol (TFE)] done by Wright et al (12) and Borgia et al (14), in which the number of monomers involved in the critical step for initial aggregation was inferred to be 2.…”
Section: Strong Interdomain Interactions Between Unfolded Domains Drivesupporting
confidence: 91%
See 2 more Smart Citations
“…The mutant dimer and trimer constructs maintain marginal stability. Our result for the wild-type construct is consistent with the aggregation experiments on I27 under denaturing conditions [28% Trifluoroethanol (TFE)] done by Wright et al (12) and Borgia et al (14), in which the number of monomers involved in the critical step for initial aggregation was inferred to be 2.…”
Section: Strong Interdomain Interactions Between Unfolded Domains Drivesupporting
confidence: 91%
“…The tetramer appears to be a critical size for the mutant construct insofar as the relative population of the misfolded state increases abruptly when going from I27 Ordered vs. Amorphous Aggregation. Borgia et al (14) note that no fibers were observed during the aggregation of I27. Instead, the aggregate that does form remains amorphous over several months, and the kinetic data can be fitted well using a model wherein the rate of aggregation is proportional to the surface area of the aggregate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The best studied of these conditions include amyotrophic lateral sclerosis (superoxide dismutase), Parkinson's disease (α-synuclein), serpinopathies (α1-antitrypsin), cancers with P53 and P21 tumor suppressor defects, and lens cataract (crystallins) (1)(2)(3)(4)(5). Some of these aggregates contain the well-known amyloid structure, and others do not; even in cases where amyloid is the final aggregated state, oligomers, prefibrillar species, and amorphous aggregates are often closely linked to pathology (6,7). Structures and interactions of specific locally unfolded or misfolded intermediate states are critically important in the mechanisms of non-amyloid aggregation (1).…”
mentioning
confidence: 99%
“…Generally, however, especially at physiological temperature and pH, p53 forms amorphous aggregates, which still contain the β-structural elements responsible for ThT binding and other properties (28,29). Amorphous aggregates are very commonly found, but there are few systematic studies of their mechanism of formation (30). We are analyzing the mechanism of amorphous aggregation of p53 in its own right, as well as to aid in the design of inhibitors (31).…”
mentioning
confidence: 99%